Um olhar especial sobre a matemática financeira aplicada ao ensino médio - Gonçalves, Cecilia Cleude (2017)
This paper presents an alternative proposal to teach financial mathematics, focusing on the decision-making power of the consumer in the face of a purchasing situation. In order to reach this goal, we have proposed an analysis from the current circumstances of the Brazilian economy, examples of how financial mathematics influences people’s lives to the theoretical assumptions underlying the development of this work. Among the contents of financial mathematics we study those that are prerequisites for the proposed study. With regard to the applications and suggestions is the report of the pedagogical workshop held with the students of the second year of high school of the State College Professor Geraldo Ribeiro da Silva; Recommendation of the use of mobile applications to monitor daily finances and, finally, what is innovative about financial education in Brazil.